Comportamiento sexual en gestantes y su influencia en infecciones genitourinarias en usuarias atendidas en consulta externa del Hospital Sagrado Corazón de Jesús Quevedo - noviembre 2023 - abril 2024. - Lerma Chimborazo, Jenny Michelle (2024)
Sexual behavior in human beings causes a lot of interest, since several emotional, social, personal, psychological factors, among others, intervene; This depends a lot on the relationship as a couple, as well as the current state and situation of the person. It must be taken into account that the sexual behavior of a pregnant woman changes significantly due to the presence of genitourinary infections, which negatively influence their sexual behavior, whether due to pain, inflammation, insecurities or simply insecurities and lack of sexual interest in your partner. The present study is descriptive - observational, the purpose of which is to analyze the influence of genitourinary infections on the sexual behavior of pregnant women treated in the outpatient consultation area of the Sagrado Corazón de Jesús de Quevedo hospital in the period November 2023 - April 2024. To This research was carried out on a total of 300 pregnant women who, after analyzing and demonstrating whose statistical data, we managed to confirm our hypothesis, and we can say that genitourinary infections do influence the sexual behavior of pregnant women. We also noticed the lack of knowledge in pregnant women about genitourinary infections and that this affects their sexual desire, for which we decided to make an academic proposal to promote training on the prevention of genitourinary infections and methods to improve sexual behavior in women, before, during and after pregnancy, to reduce obstetric risks and strengthen sexual desire in the outpatient consultation area of the Sacred Heart of Jesus Hospital. The purpose of which is to provide correct information about genitourinary infections through training to health personnel, so that they can transmit the same to the users treated in the outpatient consultation area of the Sacred Heart of Jesus Hospital.